2017
DOI: 10.1038/srep43620
|View full text |Cite
|
Sign up to set email alerts
|

Excessive fruit consumption during the second trimester is associated with increased likelihood of gestational diabetes mellitus: a prospective study

Abstract: This study aimed to investigate the association between fruit consumption during the second trimester and the occurrence of gestational diabetes mellitus (GDM). A prospective study with 772 female participants was conducted in China from April 2013 to August 2014. Dietary intake was assessed in face-to-face and telephone interviews using a 3-day food record. GDM was ascertained using a standard 75 g 2 hour oral glucose tolerance test. Multivariable logistic regression was used to estimate odds ratios (ORs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…According to the report of International Diabetes Federation (IDF) 4 , the total prevalence of GDM reaches almost 1% to 14% worldwide in 2014. In China, the recorded prevalence of GDM has increased from about 5% to more than 16% since the implementation of a new method of diagnosing GDM in December 2011 5 . Moreover, GDM increases the risk of development of type 2 diabetes mellitus in both mother and child 6 , is also associated with adverse short-term fetal outcomes and offspring long-term greater adiposity.…”
Section: Introductionmentioning
confidence: 99%
“…According to the report of International Diabetes Federation (IDF) 4 , the total prevalence of GDM reaches almost 1% to 14% worldwide in 2014. In China, the recorded prevalence of GDM has increased from about 5% to more than 16% since the implementation of a new method of diagnosing GDM in December 2011 5 . Moreover, GDM increases the risk of development of type 2 diabetes mellitus in both mother and child 6 , is also associated with adverse short-term fetal outcomes and offspring long-term greater adiposity.…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed that excessive fruit consumption was also related to GDM risk [17]. In our study sugar sweetened beverages as a part of Western dietary pattern were also associated with GDM risk, while fruit consumption was found to be beneficial.…”
Section: Discussionmentioning
confidence: 51%
“…Research has suggested that increasing vegetable and fruit consumption helps with weight loss, which might indirectly reduce the type 2 diabetes mellitus incidence (46) ; however, some meta-analyses found no relationship between fruit and/or vegetable consumption and diabetes risk (47,48) . Huang et al (49) showed that fruits with a moderate or high glycaemic index were positively associated with the occurrence of gestational diabetes mellitus. Therefore, consuming more fruits and vegetables may not help prevent diabetes.…”
Section: Discussionmentioning
confidence: 99%